The method of scattered electron spectrum division into resonance and quasielastic parts in the energy region of giant resonances - Denyak, V.V.; Khvastunov, V.M.; Paschuk, S.A.; Schelin, H.R. (Вопросы атомной науки и техники, 2005)
The pioneer method for extraction of quasielastic part from the spectrum of scattered electrons is proposed. The essence of the method is in simultaneous multipole analysis of the mix of quasielastic and resonant formfactors. The identification of resonant peaks and quasielastic part of the formfactor have been held not in scattered electron spectra but in the transition probability energy dependence of each multipolarity where there difference between resonant and quasielastic processes is clear. The pure quasielastic spectrum for ⁶⁵Cu with the electron energy E₀ =225 MeV and scattered angle θ=65° was obtained as a result of the application of this method.